"Based on a true story" podcast: a journey into the world of young patients with cancer. Issue 5 (October 2022) - Ferrari, Andrea; Silva, Matteo; Facchetti, Gianfelice; Patriccioli, Alice; Grampa, Paolo; Casanova, Michela; Livellara, Virginia; Signoroni, Stefano; Clerici, Carlo Alfredo; Massimino, Maura
This article describes a creative project undertaken by a group of adolescent and young adult patients with cancer as part of the Milan's Youth Project, a scheme dedicated to young patients with cancer with the dual aim of optimizing medical aspects of their care and promoting a holistic approach to their needs. The project was based on audio recordings and focused on the theme of "the journey, " such as a holiday or an adventure, or as a metaphor of the cancer experience. The podcast installments were published on the main streaming platforms. Talking about their disease and how they feel is of importance for young patients to process their feelings surrounding the cancer experience and to find the inner resources they need to facilitate coping.